Correlation between Shear Wave Velocity Assessed by Elastography and Stiffness given by Tensile Test in the Ovine Patellar Tendon - F, Kayser; E, Bori; N, Armillotta; B, Innocenti; F, Hontoir; JM, Vandeweerd (Archives of Clinical and Biomedical Research, 2022)
Background: Tendon injuries are very common in man, healing process often slow and incomplete, and available treatment options unsatisfactory. Mechanical properties such as stiffness can reflect the progress of tissue healing over time. Unfortunately, these measures cannot be recorded in vivo due to the invasive nature of the available conventional biomechanical testing methods. SWE can be used in vivo to investigate mechanical properties of tendons. Before clinical acceptance, SWE must be compared to tensile test values. The aim of our ex vivo study was to investigate whether SWE performed in vivo was correlated to stiffness assessed by an ex vivo uniaxial tensile test considered as gold standard. Material and methods: Twelve patellar tendons in six healthy ewes underwent conventional ultrasound, color Doppler ultrasound and SWE in vivo followed by uniaxial testing performed ex vivo. Results: The mean stiffness value of the 12 tendons was 45.69 N/mm (SD+/- 14.56). The mean shear wave velocity was 6.27 m/s (SD+/-0.6). There was a not statistically significant positive correlation between shear wave velocity and age (r=0.137, p=0.79), and a significant positive correlation between stiffness and SWV (r=0.87; p=0.02). Conclusion: SWE can be a surrogate to biomechanical properties of the tendon with the advantage that it can be performed in vivo. It could be a useful imaging tool in the context of disease progression and healing follow-up. The SWV values obtained in our study could be considered as baseline values for further research studies on patellar tendons in the ovine model.